2017
DOI: 10.18203/2319-2003.ijbcp20170941
|View full text |Cite
|
Sign up to set email alerts
|

A study of adverse drug reactions among pulmonary tuberculosis patients treated under dots in a tertiary care hospital

Abstract: Background: DOTS under RNTCP is the current treatment available for Pulmonary Tuberculosis. This treatment exhibit a greater level of efficacy with a small degree of toxicity. The present study aims to determine demography of patients with pulmonary tuberculosis and to study the ADRs caused by anti tubercular drugs and to assess the causality and severity of the reported ADRs.Methods: We studied cases of Pulmonary Tuberculosis diagnosed and treated under category I DOTS at Department of Pulmonary Medicine for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
2
0
0
Order By: Relevance
“…24 Nearly half of the patients were smear positive for AFB. This was consistent with a study conducted by Priyadarshini et al 18 In contrast to our finding, 37.81% TB patients were found to be smear positive by Prakasha et al 10 First line ATD were given to most of the patients in our study. This shows low prevalence of drug resistance in our study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…24 Nearly half of the patients were smear positive for AFB. This was consistent with a study conducted by Priyadarshini et al 18 In contrast to our finding, 37.81% TB patients were found to be smear positive by Prakasha et al 10 First line ATD were given to most of the patients in our study. This shows low prevalence of drug resistance in our study.…”
Section: Discussionsupporting
confidence: 93%
“…This finding was in accordance with that of Prakasha et al in which 58.7% cases were PTB. 10 Similar findings were also reported by Priyadarshini et al 18 However, Thakur et al had reported a high prevalence (80.3%) of PTB. 19 Tubercular lymphadenitis was the most common type of EPTB in our study and similar findings were also reported by Thakur et al in which lymph node was most commonly involved.…”
Section: Discussionsupporting
confidence: 82%